2021
DOI: 10.3390/su13179808
|View full text |Cite
|
Sign up to set email alerts
|

Lime and Organic Manure Amendment: A Potential Approach for Sustaining Crop Productivity of the T. Aman-Maize-Fallow Cropping Pattern in Acidic Piedmont Soils

Abstract: Acid soil is a hindrance to agricultural productivity and a threat to food and environmental security. Research was carried out to assess the impact of lime and organic manure (OM) amendments on yield and nutrient uptake by using the T. Aman-Maize-Fallow cropping pattern in acid soils. The experiment was set up in an RCBD design and used nine treatments and three replications. The treatments, comprising of various doses of lime, OM (cow dung and poultry manure), and a lime-OM combination, were applied to the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 52 publications
3
6
0
Order By: Relevance
“…Nitrogen is the most important yet limited nutrient among chemical fertilizers worldwide due to very low NUE due to gaseous losses such as denitrification, volatilization, and leaching from agricultural cropping systems [78,79]. Our results showed that the combined application of organic manure, inorganic fertilizer and dolomite significantly increased total crop yields (i.e., system productivity) of the cropping patterns (Tables 5 and 9), which is consistent with previous studies in acidic soil [7,24,25]. In the acidic soil of Nalitabari, Sherpur, Islam et al [7,24] reported that combined application of lime, organic amendment, and chemical fertilizer increased yield and nutrient uptake of the T. Aman-Maize-Fallow and Wheat-Mungbean-T. Aman cropping patterns.…”
Section: Effect Of Ipns On Crop Yield Nitrogen Uptake and Nitrogen Use Efficiencysupporting
confidence: 92%
See 3 more Smart Citations
“…Nitrogen is the most important yet limited nutrient among chemical fertilizers worldwide due to very low NUE due to gaseous losses such as denitrification, volatilization, and leaching from agricultural cropping systems [78,79]. Our results showed that the combined application of organic manure, inorganic fertilizer and dolomite significantly increased total crop yields (i.e., system productivity) of the cropping patterns (Tables 5 and 9), which is consistent with previous studies in acidic soil [7,24,25]. In the acidic soil of Nalitabari, Sherpur, Islam et al [7,24] reported that combined application of lime, organic amendment, and chemical fertilizer increased yield and nutrient uptake of the T. Aman-Maize-Fallow and Wheat-Mungbean-T. Aman cropping patterns.…”
Section: Effect Of Ipns On Crop Yield Nitrogen Uptake and Nitrogen Use Efficiencysupporting
confidence: 92%
“…Addition of organic and inorganic fertilizers significantly increased soil TN in acidic soil (Table 4), which aligns with Islam et al [7,24,25] and Van Chuong [67]. Previous research showed that the C:N ratio of the manure is essential for mineralization and the build-up of SOC and TN, and that a low C:N ratio boosts the mineralization process, resulting in increased soil TN [68,69].…”
Section: Effect Of Ipns On Soil Physicochemical Propertiessupporting
confidence: 86%
See 2 more Smart Citations
“…With the addition of lime and manure, any of the following mechanisms or combinations might have produced the rise in soil pH: proton consumption by functional groups associated with biological molecules [41], decarboxylation of organic acid anions during decomposition, specific adsorption of organic molecules by ligand exchange with the release of OH [42], and the release of OH ions during reduction reactions associated with localized anaerobic microsites are all examples of proton consumption [43]. STN and available P content in soil rose due to higher soil pH [44][45][46]. They increased P mineralization resulting from lime and manure treatment, as Van Chuong [47] and Naher et al [48] previously observed.…”
Section: Discussionmentioning
confidence: 99%